Pengembangan Perangkat Pembelajaran IPAS Model Guided Inquiry untuk Melatihkan Keterampilan Proses Sains dan Meningkatkan Hasil Belajar Siswa X FKKSMK Muhammadiyah 5 Babat - Sumarni (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
This research was done by developing science learning materials (lesson plans, student’s worksheets, student’s book, and learning achivement test) based on guided inquiry learning model using 4D development model to facilitate student’s science process skills and improving student’s learning achivement on environmental space connectivity. The objective of this research was to trial learning materials in 35 of junior high school’s students with one group pretest-postest design. Results were analyzed by descriptive quantitative-qualitative are: (1) Validity of learning material valid category (3.00); (2) Practicality based on: a) Feasibility of instruction good category (3,8); b) Readability of worksheets and student’s book students stating that the content and appearance of worksheets and student’s book is interesting; c) The response of students very positively (85.6%); (3) Effectiveness based on: a) Student’s activities who stand out were practice science process skills is high category (38,5%); b) Student’s science process skill in very high category as shown by student’s worksheet achivement (3,46); c) student learning achivement increased (N-Gain: 0.2-1.0). The conclusion of this research that science learning material depeloped base on guided inquiry learnig model, eligible to facilitate student’s science process skills and improve student learning achivement in junior high school.